KITAB AT-TAFSIR LI ASY-SYAIKH AHMAD BASYIR AS.: Kajian Metodologi Tafsir dan Konten Ayat - Mukhlish; Mahmudi (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2024)
Jargon – al Quran as a book of shalihun li kulli zaman wa makan – is undeniable, for the simple reason that it gets Allah’s legality in His words. For Muslims, this jargon is not merely as information (kalam khabari), but as an order (amr) to learn and keep. Therefore, KH. Ahmad Basyir As. writes a book of interpretation that can be learned by Muslims without any capacity and capability to interpret. This research is meant to answer two things: first, how is the used method in the interpretation by KH. Ahmad Basyir AS.? Second, how is the content of the interpreted verses? To make ease of that, the writer uses qualitative study or literature review, collecting books or classical books concerning the theme, including interpretation books hadits, and the explanation of ulama who are expert in it. While, for several data about the interpreter, the writer makes interview some informants. This research results are as follows: first, the interpreting sources in the interpretation of KH. Ahmad Basyir AS. is bi al-ra’yi. Second, the interpreting method is a global method (ijmali) and thematic (maudhu’i). Third, the interpretive style is fiqhi style (part 2-interpretation) and lughawi (part 1-interpretation). Fourth, the used systematic interpretation is maudhu’i. Furthermore, the interpreted contents are kauniyah verses, mawaris verses, munakahat verses, verses about the law of good and bad food and drink, and verses about the law of slaughter. Keywords: Interpretation Methodology; Verse Contents; KH. Ahmad Basyir AS.